Modern science communication in a global context: perspectives on nanotechnology from Swedish, Polish and Iranian press coverage - Lemańczyk, Szczepan Jan (2013)
The study of media coverage of emerging technologies constitutes an important field in Science and Technology Studies. Nanotechnology is one of these emerging technologies. Traditionally, research has focused on media coverage in developed countries, especially English-speaking ones - the United States, Canada and United Kingdom. This thesis breaks with this tradition. It is an attempt to "de-westernize" this area of research by moving the focus towards Sweden, Poland and Iran – countries that differ considerably from each other in terms of economy, culture, religion, technological development or socio-political system. More importantly, these countries have never been studied in this context before. Qualitative content analysis of the articles published between 2004 and 2009 in seven Swedish, Polish and Iranian daily newspapers has been conducted in order to determine cross-national differences in the debates on nanotechnology, in terms of frames, themes, metaphors or sources. A parallel aim was to assess how socio-political differences may influence media reporting on nanotechnology or how the discussion of nanotechnology reflects socio-political differences. The results shows that although media coverage of nanotechnology in Sweden, Poland and Iran largely followed the patterns observed in other countries, there are elements that are characteristic of Poland, Sweden or Iran alone. The most specific one is the use of nanotechnology in order to promote a country's image, enhance its international reputation externally or strengthen national pride internally. Additionally, this research suggests improvements to some of the earlier approaches used in the studies of media coverage of emerging technologies. Considering the current discussions around the importance of 'nano communication', this thesis contributes not only to the study of media coverage and public perceptions of emerging technologies within Science and Technology Studies but also to particular areas of other disciplines such as culture and media studies and philology.